Saúde, professor/a!: do perfil do adoecimento docente às repercussões na prática pedagógica - Andrade, Maria José Silva (2007)
The educator sickness and its possible repercussions in the pedagogical practice. It is pointed out the articulations among the Brazilian Teaching Organization, the educational reforms, partially deriving from the situation in which the capitalism is, and the incidences related to the organization and management of the school, in order to understand the alterations on the work of the teachers and on the processes of health-sickness in the school context, trying approaches to the notion of subjectiveness to evidence answers signaled as its effects. The objective is to build a sickness profile of the teachers of the County Educational System, from São Luís, in order to identify its possible impacts on the pedagogical practice in the class room, pointing out organizational and environmental characteristics indicated by the teachers as aspects that can favor wearing out situations, enunciating the situation of sickness and its effects on the amount of medical licenses and sick leave and revealing the movements of attention and reaction to the worsening of the teachers health. The theoretical references presents contributions of researchers such as: Antunes (2001, 2004), Oliveira (2000, 2002, 2003), Freitas (2001), Silva (2002), Esteve (1999), Codo (2002), Martinez (2003), Araújo and Paranhos (2003), Araújo et al. (2005), Gasparini, Barreto and Assumption (2005), Bardin (2004), among others. Other contributions were also searched, highlighting on Foucault (2003, 2006, 2007) power-knowledge about the live body, the (re)organization of the medical knowledge and the meaning of the disease; the references were also supported by Minayo-Gomez and Barros (2002) and Barros (2002, 2003) with the incorporation of the discussions on the processes of subjectiveness in the school, that contributes to other perspectives of analysis of the teachers work absences via medical licenses. A qualitative approach of research was adopted, using as procedures and instruments: documental analysis, semi-structured interview, questionnaire filled out without the presence of the researcher and without his comments. For data analysis it was considered the orientations of the Analysis of Content. As subject of the research, it was used the educators of the initial series of Elementary School of a school in the urban zone of São Luís, besides the managers, coordinators and a sample of the morning students. The main results of the study suggest attention to the presence of certain factors described as inadequate to the good working performance and facilitators of the teachers wearing out and to the intense work overload referred to by the teachers, mainly concerning to the amount of students in the class rooms, excess of activities and tasks to accomplish, pedagogical demands, use of the break time and lack of family support. It is possible to state that the data indicates an accusation of the situation of sickness in which the educator is, because among the categories that make for the municipal public service, this is the one that is the most absent of work because of medical licenses.The teachers sickness profile is characterized by high incidence of diseases, especially those related to the osseous-muscular system and the conjunctive tissue, followed by mental and behavior disturbances, diseases of the respiratory and circulatory systems and neoplasias. A high percentage of extended sick leaves were noticed, indicating a continuous absence of an educator, besides the association of diagnoses for the same license, in other words, the teacher not only just gets sick, but also he/she gets sick for several causes. It was observed that in the school, contradicting the indexes, in spite of being sick, the educator, in some cases, remains in the classroom, as if resisting to be away from it. Inferences concerning the repercussions of this sickness in the pedagogical practice allow to associate them to components such as planning, professor/student relationship and evaluation, indicating that it does not isolate itself and it is not immune to the worsening of the teachers health. It can be stated that some observed actions, perhaps insignificant for the teachers, are in fact movements of struggle and reaction against the sickness situations, movements that differ from each other according to the capacity of each one of them to understand and fight against their sickness. Keywords: Teachers work. Sickness. Pedagogical practice.